STUDI KOMPARASI FRAMEWORK NIST DAN ISO 27001 SEBAGAI STANDAR AUDIT DENGAN METODE DESKRIPTIF STUDI PUSTAKA - Hendi Sama; Licen Licen; Jodi Saputra Dermawan Saragi; Meiliverani Erline; Kelvin Kelvin; Yudi Hartanto; Jenry Winata; Melvy Devalia (LPPM Universitas Abdurrab, 2021)
The rapid development of information technology has had various positive impacts on companies that implement it in order to achieve their vision, mission, and goals. However, the benefits of the development of information technology also carry various threats and risks of its use. One of the risks referred to is cyber attacks. There are various standard frameworks that can be used to audit/measure the level of cybersecurity security, including NIST and ISO 27001. The purpose of this study is to make a comparison of the cybersecurity framework standards NIST and ISO 27001 with descriptive literature study methods. The results of this study obtain the advantages and disadvantages of each standard framework.